Unicode encryption and its role in facilitating writing Quran using the computer - Abudena, Mussa A.; Hameed, Shihab A.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran (The Institute of Electrical and Electronics Engineers, Inc., 2016)
There is high need for data encryption. Accordingly, there are several techniques to encrypt and encode data. Unicode has become a unified global coding system. The special feature of Unicode system is that it can be expanded and it is adopted by many computer fonts’ ready-package programs. This research work uses FontCreator program, which adopts unified global coding system, to generate computer font to write the Quran according to ALDANI Uthmanic script. The explanation of the technique to write one page of Quran using this font is highlighted. Analysis of time estimation to write the whole Quran is presented.